MODEL PENGEMBANGAN AGROINDUSTRI SORGUM MENDUKUNG DIVERSIFIKASI PANGAN: STUDI KASUS DI KABUPATEN FLORES TIMUR, PROVINSI NUSA TENGGARA TIMUR - Mulyawanti, Ira; Suryana, Esty Asriyana; Winarti, C H; Munarso, S Joni (Analisis Kebijakan Pertanian, 2024)
Food diversification is one of feaseable ways to overcome the threat of a food crisis, which is currently occurring due to climate change and geopolitical tensions. Non-rice and non-wheat food sources have the potential to to support food diversification, one of which is sorghum. Sorghum is easy in terms of cultivation because it has a fairly high tolerance to its growing environment. Sorghum is also rich in nutrients and has functional components beneficial to health. The aim of this research is to formulate a sorghum agroindustry development model with a case study in East Flores District, East Nusa Tenggara (NTT) Province. The analysis was conducted through field observations, technology intervention, interviews, coordination, and several focused group discussions. The results showed that sorghum agroindustry development could be applied to the entire sorghum value chain. Improving and strengthening institutions' capacity was found to be an important key strategy to support East Flores District as a center for the development of sorghum-based local food. Increasing the role and capacity of farmer groups and farmer cooperatives are the main leverage for the success of strengthening sorghum farmer corporations. Socialization, promotion, and development of sorghum-based food producers/outlets need to be expanded and strengthened in East Flores and also in Kupang City, as the capital of East Nusa Tenggara Province,  to expand the marketing access of foods sorghum-based outside the province.